TRABALHO DOCENTE E APOSENTADORIA: O CASO DA UNIVERSIDADE DE LISBOA, PORTUGAL | Faculty members’ work and retirement: the case of the University of Lisbon – Portugal (Trabalho & Educação, 2018)
The study seeks to understand the motivations of female faculty members – both retired and those who fulfil legal retirement requirements – to remain at work. The research is qualitative and comprises a documentary analysis of the legislation on the career of university professors in Portugal. It is part of a case study with empirical research with four female faculty members from the University of Lisbon. Data analysis considered the concepts of work issued by Dubar (2012), the concepts of work intensification and deterioration of work conditions by Dal Rosso (2008), as well as findings of researches about faculty members and retirement that have been carried out both in Brazil and Portugal. The findings indicate that the participants’ motivations for remaining at work have to do with their vitality and satisfaction with work; to the possibility of keeping their labor activities with autonomy and freedom, which results in more non-working activities – including leisure ones. The retired participants emphasized that they only remain at work because by so doing they do not prevent the entry of new professors into the career. They also called on the importance that knowledge based on experience has in the transition from the old to the new to justify their choice to remain at work.___O estudo busca compreender as motivações de professoras aposentadas e em condições legais de aposentação para a permanência no trabalho organizacional. A investigação, cuja metodologia se inscreve em uma abordagem qualitativa, envolve pesquisa documental sobre a legislação da carreira do professor universitário em Portugal e se inscreve em um estudo de caso com pesquisa empírica com quatro professoras da Universidade de Lisboa. A análise dos dados tomou os conceitos de trabalho em Dubar (2012), intensificação do trabalho em Dal Rosso (2008) e precarização, além dos achados nas pesquisas sobre professores universitários e aposentadoria, no Brasil e em Portugal. Os resultados indicam que as principais motivações para a permanência se vinculam à vitalidade e satisfação com o trabalho; à possibilidade de continuar em atividade laboral com autonomia e liberdade, o que resulta em mais tempo para o não trabalho, o que inclui o lazer. As participantes aposentadas ressaltaram que só permanecem porque não estão a impedir o ingresso dos mais jovens, além de justificarem a permanência pela importância que o conhecimento fundado na experiência possui na transição entre o antigo e o novo.